Investigation of Heat Transfer Characteristics of Molten Slags - G. G. Krishna Murthy (The Minerals, Metals and Materials Society, 1993)
Several experiments were conducted to determine the rates of heat transfer coefficients of CaO-SiO2-A1203-FeO slags at temperatures in the range 1623-1823 K The experimental technique involved measuring heating rates of a solid specimen, sub¬merged in slag phase, using a temperature probe made of Pt\ 10%Rh-Pt. Effect of %FeO (3-10%), %FeS (0.1-0.68%), %P205 (0.2-3.0%), %MgO(5-6%), and %MnO (0.96-3.84%) present in the slag on overall heat transfer coefficient, U, of slags was investigated. Simple first order heat balance equation in combination with experimental plots rising temperature of solid specimen versus time were employed to determine the values of U. The values of U determined in the present investigation were present in the range of 70-260 cal/Ks.m2. The value of U increased with increasing the slag temperature. The values of U were not effected by increased amounts of sulfur in the slag phase. The increased concentrations of MgO, FeO, MnO, and P205 in the slag phase decreased the values of U. On the other hand, the increased amounts of Fe2O3 in the slag phase increased the value of U. Comparison of the results, obtained using the slag bath stirred by argon injection, with those determined without any stirring indicated that both radiative and conductive heat transfer mechanisms are important even at high temperatures.